2018
DOI: 10.3389/fpsyt.2018.00071
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Glucose and Fructose Administration on the Neural Correlates of Cognitive Functioning in Healthy Subjects: A Pilot Study

Abstract: The present randomized double-blinded cross-over study aims to extensively study the neural correlates underpinning cognitive functions in healthy subjects after acute glucose and fructose administration, using an integrative multimodal neuroimaging approach. Five minutes after glucose, fructose, or placebo administration through a nasogastric tube, 12 participants underwent 3 complementary neuroimaging techniques: 2 task-based functional magnetic resonance imaging (fMRI) sequences to assess working memory (N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…In addition, Zanchi el al. [44] observed increased functional connectivity in networks related to cognitive functions after acute fructose intake.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zanchi el al. [44] observed increased functional connectivity in networks related to cognitive functions after acute fructose intake.…”
Section: Discussionmentioning
confidence: 99%
“…The studies were conducted in several countries including UK (n = 3), Canada (n = 2), USA (n = 2), Australia (n = 1), Spain (n = 1), Switzerland (n = 1) and Korea (n = 1). Six studies were conducted with healthy adult participants (An, Jung, Kim, Lee, & Kim, 2015;Brown & Riby, 2013;Parent et al, 2011;Riby et al, 2008;Serra-Grabulosa, Adan, Falcon, & Bargallo, 2010;Zanchi et al, 2018). Three studies were conducted with healthy elderly samples (Gagnon et al, 2012;Knott, Messier, Mahoney, & Gagnon, 2001;Scholey et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported spectral analysis of resting EEG (An et al, 2015;Knott et al, 2001). Four studies were conducted using task related functional magnetic resonance imaging (fMRI: Parent et al, 2011;Serra-Grabulosa et al, 2010;Stone et al, 2005;Zanchi et al, 2018), of which two also reported measuring fMRI connectivity (Parent et al, 2011;Zanchi et al, 2018). One study was conducted using functional near infrared spectroscopy (fNIRS: Gagnon et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations